Desempenho e Características de Carcaça de Novilhos Suplementados no Período das Águas - Zervoudakis, Joanis Tilemahos; Paulino, Mário Fonseca; Detmann, Edenio; De Paula Lana, Rogério; De Campos Valadares Filho, Sebastião; Cecon, Paulo Roberto; De Queiroz, Domingos Sávio; Moreira, Andréia Luciane [UNESP] (My University, 2001)
The effects of concentrate supplementation of steers during the rainny season on the performance and physical and traits of the carcass were evaluated. Fourty nine crossbreds steers were used, maintained on pastures of Brachiaria decumbens. The experiment was carried out in three experimental periods, according to a complete randomized design. The following supplements were daily fed at 10a.m.: mineral salt (SALT), corn and soybean meal based supplements, with 20% CP, at the levels of 1.0 and 2.0 kg (CSBM1 and CSBM2) and wheat bran and soybean meal based supplements, with 20% CP, at the levels of 1.0 and 2.0 kg (WMSBM1 and WMSBM2). There was no treatment effect on average daily gain (ADG) and body weight (BW). The ADG were: 0.887, 0.936, 1.047, 0.943 and 1.012 kg/animal/day, respectively, for the treatments SALT, CSBM1, CSBM2, WMSBM1 and WMSBM2. The animals submitted to the different treatments did not exhibit differences in the physical and chemical characteristics of the carcass. No differences were observed for the steers carcass yield, which was, in average, of 52.19%.
Performance and Characteristics of Carcass of Supplemented Steers during the Rainny Season
Keywords: Body composition; Braquiaria; Finishing; Supplements